Sex-habit and Sexually Transmitted Infection (STIs) Among The Drug Abusers Undergoing Detoxification - Hossain, Kazi Jahangir; Karim, Md. Rizwanul; Karim, Abul Masud Md. Nurul; Kamal, Md. Mustafa (Journal of Medicine, 2013)
Drug abuse is increasing alarmingly with time among the young-adults in Bangladesh. The objective of the study was to investigate sex-habit and STIs of the drug abusers. A total of 1076 drug abusers undergoing detoxification voluntarily at the Central Drug Addiction Treatment Centre (CTC), Tejgaon, Dhaka were investigated from September 2010 to August 2011. They were selected consecutively on the basis of defined selection criteria. Research instrument was an interviewer questionnaire and blood specimen. Results showed that 82.1% (n=883) were heterosexual and 16.2% (n=174) had no sex. The majority of them (55.3%, n=595) had enjoyed sex with multiple partners. They enjoyed sex with commercial sex sellers (11.1%, n=119) but majority of them (34.2%, n=368) had sex with all categories including spouse. Results also showed that majority of them had unethical sex, of which 24.9%(n=268) had experience about extramarital sex and 30.4%(n=327) premarital sex respectively. Around 55.0%(n=594) of them did not use condom during sex and 21.9%(n=236) used it occasionally. The 14.5%(n=156) of them had signsymptoms of gonorrhea and syphilis, of which 1.8%(n=19) had genital ulcer, 3.7%(n=40) genital discharge and 9.0%(n=97) had both ulcer and discharge respectively. In laboratory analysis, 16.3%(n=175) had STIs positive results, of which 9.9%(n=107) were RPR reactive, 1.8%(n=19) URS reactive and 4.6%(n=49) both RPR and URS reactive respectively. In drug habit, results also showed that 82.6% (n=889) of them had been using heroin and the rests used cannabis (8.6%, n=93), phensedyl (5.4%, n=58) and injections (3.3%, n=25) respectively. Forty two percent (n=455) of them had been abusing it for 1-5 years, 31.4% (n=338) for 6-10 years and 26.3%(n=283) for 11-20 years. Most of them (91.1%, n=980) used multiple illicit drugs and their ultimate choice of drug was heroin (77.3%, n=832). About 22.6%(n=243) addicts abused injection drugs in their lifetime. Altering behaviors, especially their drug habit and sexual lifestyle are still the only applicable ways to stop this human catastrophe. DOI: http://dx.doi.org/10.3329/jom.v14i1.14529 J MEDICINE 2013; 14 : 5-10